Hubungan Dokter dengan Pasien Dalam Bidang Kesehatan - Bing Waluyo (Wijayakusuma Law Review, 2023)
The relationship between doctors and patients begins with a vertical, paternalistic relationship pattern, which isbased on the principle of father knows best, which gives birth to a paternalistic relationship. The position/position ofthe doctor and the patient are not equal, namely the position of the doctor is considered higher than the patient,because the doctor is considered to know best about all kinds of diseases and how to cure them, while the patient isconsidered to know nothing about the disease and he submits it completely to the doctor. Doctors are placed aspatrons (protectors) and patients are placed as clients (protected people). Then, in its development, the vertical,paternalistic relationship pattern shifted to a horizontal, contractual relationship pattern. This relationship givesbirth to a horizontal contractual legal aspect which is inspanningsverbintenis which is a legal relationship betweentwo legal subjects (patients and doctors) who are of equal status, giving rise to rights and obligations for the partiesconcerned. This legal relationship does not promise anything (healing or death) because the object of the legalrelationship is the maximum effort made by the doctor carefully and with tension based on his knowledge andexperience in treating illnesses to cure the patient's illness.Keywords: Juridical Review, Relationship, Doctor and Patient, Health Sector